The Effect of Learning Interest And Motivation on Mathematics Learning Outcomes of Students of Class VIII SMP Private Cinta Rakyat 3 Pematangsiantar - Simorangkir, Rosari Angelia; Sidabutar, Ropinus (Lembaga Riset Mutiara Akbar, 2022)
This study aims to determine: (1) the effect of interest in learning on students' mathematics learning outcomes in grade VIII SMP Swasta Cinta Rakyat 3 Pematangsiantar Academic Year 2022/2023. (2) the effect of learning motivation on students' mathematics learning outcomes in class VIII of Cinta Rakyat 3 Pematangsiantar Private Junior High School in the Academic Year of 2022/2023. (3) the effect of interest and learning motivation on students' mathematics learning outcomes in class VIII of Cinta Rakyat Private Junior High School 3 Pematangsiantar for the Academic Year of 2022/2023. This type of research is a quantitative research type with the research sample being students of class VIII B and VIII C SMP Swasta Cinta Rakyat 3 Pematangsiantar, namely 60 students. The instruments used in this research are questionnaires and tests that have been tested for validity and reliability tests. The results and discussion of the research show that: (1) There is a positive and significant relationship between interest in learning and mathematics learning outcomes for class VIII students of SMP Swasta Cinta Rakyat 3 Pematangsiantar, with a value of t_count > t_table (3.500 > 2.001) and a large effect of 17.4%. (2) There is a positive and significant relationship between learning motivation and mathematics learning outcomes for eighth grade students of Cinta Rakyat 3 SMP Swasta Cinta Rakyat 3 Pematangsiantar, with a value of t_count > t_table (4.101 > 2.001) and a large effect of 22.4%. (3) There is a positive and significant effect between interest in learning and motivation to learn together with the value of F_count > F_table (10,865 > 3.115) and a large effect of 27.6%.